Deciphering the diagenetic alteration degree in thrombolites across the Permian-Triassic boundary and the evaluation of REY as a proxy of palaeoseawater - Li, Rong (Journal of Asian earth sciences, 2017)
[Display omitted] •The Cili and Taiping thrombolites varied from digitate to mottled across the PTB.•The digitate Cili thrombolites were subject to stronger diagenetic alterations.•Higher REY contents were present in the mottled thrombolites from Taiping section.•The La and Ce anomalies in Cili thrombolites have been altered by terrigenous input.•The Taiping thrombolites are better proxy candidates for palaeoseawater properties. The thrombolites across the Permian-Triassic boundary (PTB) are widely distributed in South China. In order to examine the utility of rare earth element and yttrium (REY) in the thrombolites as a proxy of palaeoseawater, the petrographic and geochemical (Sr, Mn, Fe, REY, δ13C, δ18O) features of thrombolites from Cili and Taiping sections are comparatively studied to determine the diagenetic alteration degrees of the thrombolites and the impact of diagenesis on REY concentrations and distribution patterns. The thrombolites from Cili section, digitate in mesoscopic morphology, are latest Permian in age. In contrast, most of the thrombolites in Taiping section are mottled and formed in the earliest Triassic. The variation in thrombolite morphology across the PTB is probably related to increasing amount of metazoan and increasing intensity of bioturbation after the end-Permian mass extinction. Compared to the thrombolites from Taiping section, those from Cili section underwent more extensive diagenetic alteration, which are characterized by more dolomitic content, lower Sr concentrations, more negative δ18O values, and higher Mn/Sr ratios. The REY concentrations are higher in the thrombolites from Taiping section (5–303ppm, average 48ppm) than in the thrombolites from Cili section (17–34ppm, average 25ppm). Shale-normalized REY distribution patterns of the thrombolites from both sites are similar to those of oxygenated seawater, which are characterized by positive La anomalies (Pr/Pr∗=1.1–1.5), negative Ce anomalies (Ce/Ce∗=0.2–0.9), and light rare earth element (LREE) depletion. The preserved seawater like REY distribution pattern indicates that diagenesis did not alter the REY distribution patterns. The thrombolite samples from Cili section, compared to the counterparts from Taiping, have less positive La anomaly and less negative Ce anomaly. For the thrombolites from Cili section, a positive correlation exists between Ce anomaly and siliciclastic content, suggesting contamination of Ce anomaly by terrigenous input. The results suggest that ancient thrombolites that are isolated from terrigenous inputs are better proxy candidates of palaeoseawater redox condition than thrombolites located closer to land sources.